Analisis Sistem Informasi Akuntansi Penerimaan Kas (SPP) pada Yayasan Semesta Khatulistiwa - Hendri; Muhammad Alghifari; Herlina Yani Putri; Mutia Rahayu; Nurmalasari Nurmalasari (Jurnal Sistem Informasi Akuntansi, 2025)
This study aims to analyze the accounting information system for cash receipts, specifically for the Sumbangan Pembinaan Pendidikan (SPP) payments at Yayasan Semesta Khatulistiwa. The current manual system used by the foundation often leads to inefficiencies in data recording and financial reporting. Through observation, interviews, and literature study, the researchers identified the need for a more structured and digital approach. The research employed the waterfall method in designing a prototype system using Figma, supported by UML modeling tools such as use case, activity, and sequence diagrams. The proposed system provides a user-friendly interface for recording, managing, and monitoring student payments. With the implementation of this system, the foundation is expected to improve the accuracy, timeliness, and transparency of financial data, while enhancing internal controls and decision-making processes.